The Impact of Social-media Marketing Activities on Consumers’ Loyalty Intentions: The Mediating Roles of Brand Awareness, Consumer Brand Engagement and Brand Image - M.Z A. Tarabieh, Saeed (Jordan Journal of Business Administration, 2022)
Social-media marketing activities (SMMAs) have been recently attracting marketers’ and researchers’ attention, which resulted in more research investigating these new marketing channels and their impacts. The purpose of this study is to examine the impact of SMMAs on loyalty intentions (LIs) via brand awareness (BA), consumer brand engagement (CBE) and brand image (BI). This study was conducted through an online survey on Jordanian consumers’ experience with airlines using Facebook, Twitter or Instagram. Those consumers followed the brand of at least one airline on one or more of the above-listed social-media platforms. The analytical results revealed three key findings; first, SMMAs have a significant and positive influence on BA and CBE. Moreover, BA and CBE exhibit a significant and positive influence on BI and LI. BI also has a significant positive effect on LI. Finally, the academic and managerial implications based on the empirical results of this study are provided as a reference for the improvement of social-media marketing.